Implementation of Deep Class Management Enhancing Early Childhood Creativity in Raudhatul Athfal - Sitorus, Junida Fitriani; Khadijah, Khadijah; Marina Harahap, Ida; Diyah, Siska; Syafitri, Syafitri (Universitas Islam negeri Mahmud Yunus Batusangkar, 2024)
This study aims to explore the implementation of classroom management in enhancing creativity among young children. Early childhood creativity is a crucial aspect of their development that influences innovative thinking and problemsolving abilities. Effective classroom management has the potential to be a significant factor in facilitating and enhancing creativity among young children. A qualitative research method is utilized in this study, focusing on exploring classroom management practices that support the creativity of young children. This research will involve direct observations within classroom contexts, interviews with educators, and document analysis to understand effective classroom management practices. The findings of this study are expected to provide a better understanding of the correlation between good classroom management and the development of creativity in young children. The implications of these research findings will offer practical guidance to educators in optimizing classroom management to support the development of creativity among young children. ┬á┬á┬á